Tuli pada Lingkungan Kerja - Soemadi, Rochmat (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2009)
ABSTRACT Deaf according to Indro Soetirto and Jenny Bashiruddin is loss of hearing caused by loud enough and long enough noise. Noise is defined by physicist as a voice which is caused by acoustics waves with random intensity and frequency, while according to Indro Sutirto and Jenny Bashiruddin, noise is undesirable sound and in audio logic is pure tone mixture with various frequency. The fact that workers at place with environment like blacksmith, railway maker, and weaver, industry, step by step suffers from deafness after works through years. Problem generated by noise increasing, so protection program of hearing in industry should be done. Therefore, control noise is needed to prevent from deaf in the workplace. ABSTRAK Tuli menurut Indro Indro Soetirto dan Jenny Bashiruddin adalah kehilangan pendengaran oleh karena bising yang sangat dan lama. Bising didefinisikan sebagai suara yang disebabkan oleh getaran akustik dengan berbagai intensitas dan frekuensi, dimana menurut Indro Sutirto dan Jenny Bashiruddin, bising adalah bunyi yang tidak diharapkan. Fakta bahwa pekerja yang berada dalam lingkungan bising seperti tukang pandai besi, pekerja yang bekerja di rel kereta api, industri, sedikit demi sedikit akan mengalami ketulian setelah bekerja selama beberapa tahun. Masalah yang timbul akibat ketulian terus meningkat, jadi program proteksi pekerja yang bekerja di lingkungan bising harus dilakukan, yaitu dengan pembatasan kebisingan.